Centro de desarrollo infantil ladera de colores desde una perspectiva pedagógica a través de las actividades rectoras - García García, Ana María (Universidad de San Buenaventura - Cali, 2017)
This research descriptive type made with the hermeneutics research method, gathers different observation instruments as it provides detailed information about how the CENTRO DE DESARROLLO INFANTIL LADERA DE COLORES, located in the city of Cali, is run from a pedagogical perspective through guiding activities such as art, literature, games and surroundings quest proposed by the Colombian National Ministry of Education of Colombia. The results brought together by this graduate work paper consisted on the attainment of an analysis and a comparison of that specified in the " Cero a Siempre" strategy , along with the technical administrative guidelines given by the ICBF, and what actually takes place in the institution.